Gray Area Ethical Leadership in the NCAA - Michael Sagas; Brian J. Wigley (University of Kansas Libraries, 2014)
The NCAA's operating manuals provide member institutions with hundreds of pages of bylaws that outline how member institutions should operate their athletic programs. Interpretations of these rules can lead to sanctions for student-athletes, coaches, athletic administrators and institutions. Such rule-based systems can potentially lead to the belief that simply following the rules as written equates to right or ethical behavior. In this commentary, we used an ethical leadership framework primarily built on the leadership and management thoughts of Bennis and Nanus (1985) to propose the College Athletics Ethical Leadership Continuum which can be used to assess the behaviors, rules, and decisions made by NCAA membership. Fundamental principles of this conceptual model include holding the student-athlete as the primary stakeholder of college sports activities, and that a critical analysis of the present is necessary to provide leadership for the future. Based on a distinction between doing things right and doing the right thing, the model is applied to four case studies in which NCAA membership policies and actions, or lack thereof, are likely compromising the wellbeing and academic success of student-athletes.